Evaluation of larvae production and growth of juvenile red tilapia NIFI F1 during the nursery phase - Adam Robisalmi; Priadi Setyawan; Bambang Gunadi (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2018)
Genetic quality improvement can be done through breeding programs. The indicator of success in the selection is the improvement of the character of production. Larval production and growth of NIFI of F1generation red tilapia seeds in the selection and its control parents were evaluated in this study. The research was conducted at the Fish Breeding Research Center for four months. Spawning was carried out on freshwater ponds of cage with size of 1 x 1 m. Tilapia brood stock were stocked with male to female ratio of 1: 1. The larvae rearing were conducted in the cage with size 2x2x1 m3 and stocking density 125 m-2. Pellets with a protein content of 38-40% are given to ad libitum larvae three times a day for first month, and then feeding rate was given 15-20% daily from biomass. Seed production, growth, specific growth rate, and survival rate were observed. The results of the experiment show a difference between fish selected and control. Seed production of selection reached 540 ± 114 and controls 508 ± 142. The growth performance of selected red tilapia juvenile showed higher compared with the control. The mean length of selected population reached 6.33 ± 0.43 cm , weight gain 6.60 ± 0.52 g, specific growth rate 7.33 ± 0% g days-1 and survival rate 81.50 ± 4.46% were respectively and the control population 5.76 ± 0.52 cm ; 4,90 ± 0.58 g; 4.50 ± 0.35% g days-1; and 74.85 ± 3.26%. These values indicate that the growth of red tilapia juvenile NIFI F1 generation was increased 25.76%. Abstrak Salah satu upaya yang dapat dilakukan untuk meningkatkan kualitas genetik yaitu melalui program pemuliaan. Per-baikan karakter reproduksi dan pertumbuhan dapat digunakan sebagai indikator keberhasilan seleksi. Penelitian ini bertujuan untuk mengevaluasi produksi larva dan pertumbuhan benih ikan nila merah NIFI F1 dari induk seleksi dan kontrol. Kegiatan dilaksanakan selama empat bulan di Balai Riset Pemuliaan Ikan. Pemijahan dilakukan di kolam air tawar pada hapa 1 m x1 m. Perbandingan induk ikan nila jantan dan betina 1:1. Larva yang sudah dipanen dimasukkan pada hapa pendederan ukuran 2x2x1 m3 dengan padat tebar 125 ekor m-2 . Selama pendederan , larva diberi pakan (protein 38-42%) secara ad libitum tiga kali sehari pada bulan pertama dan selanjutnya diberi pakan dua kali sehari 15-20% dari biomassa. Pakan yang diberikan selama pendederan mempunyai protein berkisar 38-42%. Parameter yang diamati meliputi produksi larva, pertumbuhan, laju pertumbuhan spesifik, dan sintasan. Hasil penelitian menunjukkan produksi larva ikan nila merah seleksi yaitu 540±114 ekor dan kontrol 508±142 ekor. Performa pertumbuhan benih ikan nila merah seleksi menunjukkan hasil yang lebih tinggi dibanding kontrol dengan nilai pertumbuhan panjang 6,33 ±0,43cm, pertumbuhan bobot 6,60±0,52 g, laju pertumbuhan spesifik 7,33±0% g hari-1 serta sintasan 81,50±4,46%, se-dangkan populasi kontrol masing-masing 5,76±0,52 cm; 4,90±0,58 g; 4,50±0,35% g hari-1; dan 74,85±3,26%. Nilai ini menunjukkan bahwa ada peningkatan pertumbuhan sebesar 25,76% pada benih ikan nila merah NIFI F1.